The RED resource : recognition - enhancement - development : the contribution of sessional teaching staff to higher education. (Council of Australian Directors of Academic Development, 2008)
This study into the recognition, enhancement and development of sessional teaching in higher education builds on the 2003 Australian Universities Teaching Committee Report. The aim of the current Project was to identify and analyse current national practice and refocus attention on the issues surrounding sessional teachers in the university sector. The Project had three objectives: to establish the full extent of the contribution that sessional teachers make to teaching and learning in higher education; to identify and analyse good practice examples for dissemination; and to consider the possible developments for institutional and sector-wide improvements to the quality enhancement of sessional teaching. Sixteen Australian universities were involved in the project representing all states and territories. At each of the participating universities, the number and typology of sessional teachers was audited across the institution and sixty interviews were conducted with the full range of participants, from sessional teachers to university executive staff. [p.2 ed]